Factors that Prevents Polygamy: A Case Study on Male teachers in the District of Kinabatangan, Sabah - Saifulazry Mokhtar; Mohd Zaidi Mustafa; Kasoma Thia; Mohd Maziz al-Hadi Moharam; Habibah Artini Ramlie (2020)
Polygamy in Islam often misunderstood by many. This resulted in the proliferation of polygamy among Muslims, and that those practices polygamy generally being accused of depicting savagery, cruelty to women, mental abuse to children, the cause of the collapse of the household, the practice of magic and so on. This study looks at the views of male teachers in the district of Kinabatangan, Sabah on the practice of polygamy as well as to identify barriers to polygamy in their social life. A total of 64 male teachers were selected based on their ability, interest and critical views over polygamy as well as their willingness to provide full cooperation. This study applies qualitative methods which focuses on interviews with selected individuals. The findings of the study show that there are two main factors that hinder male teachers in Kinabatagan to practice polygamy, namely internal factors and external factors. It suggests that the internal factors impacted male teachers significantly as compared to external factors. Thus, it portrays that to realize this desire for polygamy, various parties need to play a role in convincing men to practice polygamy which acknowledged by the society.